Laticifers in Sapindaceae: Structure, Evolution and Phylogenetic Importance - Medina, Maria Camila; Sousa-Baena, Mariane S.; Prado, Erika; Acevedo-Rodríguez, Pedro; Dias, Pedro; Demarco, Diego (Frontiers in Plant Science, 2021)
Laticifer occurrence and structure are poorly known in Sapindaceae. Occurrence is likely underestimated owing to the low production of latex in most species. We investigated 67 species from 23 genera of Sapindaceae to verify laticifer occurrence and their structural, developmental and chemical features, as well as their evolutionary history in the family. Shoots were collected from herbarium and fresh specimens for histological analyses. Three characters derived from laticifer features were coded and their ancestral states reconstructed through Bayesian stochastic mapping and maximum likelihood estimation. Only articulated non-anastomosing laticifers were found in Sapindaceae. Laticifers differentiate early during shoot development and are found in the cortex, phloem and pith. Latex is mostly composed of lipids. Callose and suberin were detected in laticifer cell walls in some genera. Reconstruction of laticifer ancestral states showed that laticifers are present in most clades of Sapindaceae with some reversals. Callose in the laticifer cell wall was found exclusively in Serjania and Paullinia (tribe Paullinieae), a character regarded as independently derived. Occurrence of laticifers in Sapindaceae is broader than previously reported. Articulated non-anastomosing laticifers had five independent origins in Sapindaceae with some secondary losses, occurring in five out of six genera of Paullinieae and 10 other genera outside Paullinieae. Particularly, callose in the laticifer cell wall evolved independently twice in the family, and its occurrence may be interpreted as a key-innovation that promoted the diversification of Paullinia and Serjania. Our study suggests that laticifer characters may be useful in understanding the generic relationships within the family.